RESEARCH ON THE CORRELATION OF MENTAL DISORDERS AND TERRORISM - Djoric, Marija (Serbian political thought, 2024)
The paper analyzes the possible connection between mental disorders and terrorism/violent extremism. Mental health is a universal human right and it is important not only for personal but also for general social development. As this topic has been very little researched, and there is a significant scientific gap, the author came to several conclusions with the help of a comparative analysis of existing empirical studies. There is a great stigmatization of people with mental illnesses, which affects the creation of certain prejudices that associate the sick with violent behavior (which is mostly incorrect). Conversely, some studies claim that mentally ill people are victims of violent behavior. Some researchers have found a link between trauma and violent extremism. In fact, trauma is often a trigger for violent extremism, and it is known that violent extremism is the first step towards the emergence of terrorism. It is very important to distinguish between certain types of terrorism and the correlation of mental illnesses. In fact, scientists are of the opinion that the tendency to mental illness is even 13.5 times higher among terrorists who act individually as lone wolves, compared to actors who are part of a terrorist group. In addition, the prevalence rate of mental illnesses among terrorists does not differ significantly compared to the general population. Radicalization that leads to violent extremism and terrorism is not a mental disorder and we cannot see it that way. An additional problem in the research of this topic is that there is no adequate cooperation between the medical profession and practitioners and theoreticians dealing with P/CVERLT, and we need to work on connecting them in order to have reliable data from this area. The conclusion is that this is still an under-researched topic due to the small number of (publicly available) empirical studies, as well as the confidentiality of the medical data of patients. In this context, each terrorist should be approached individually when assessing the mental state, although certain types of mental disorders are more common in specific types of terrorism. Attention should also be paid to the gender approach when assessing the mental health of terrorists. because there are certain differences between men and women.